2018
DOI: 10.5539/ibr.v11n3p186
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Knowledge Sharing on the Innovative Work Behavior of Employees: A Study in China

Abstract: This study is an attempt to find out the impact of knowledge sharing on the innovative work behavior of employees working in telecommunication sector of China. Particularly, the focus of this study is on the two important dimensions of knowledge sharing namely knowledge donating and knowledge collecting. For this purpose, data of 200 employees from telecommunication sector of China was collected and analyzed through correlation and multiple regression techniques. The results suggest that both knowledge donatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 27 publications
9
49
0
6
Order By: Relevance
“…The results of this study indicate that hotel management should encourage knowledge sharing behavior, especially knowledge collecting to improve their employee innovative work behavior. The significant positive relationship between knowledge collecting and knowledge donating to innovative work behavior was also found by Hu et al (2009), Kim and Lee (2013), and also by Akram, Lei, Haider, and Hussain (2018). Hu et al (2009) emphasis the role of employee knowledge sharing (symbiosis, reputation, and altruism) as determinants of innovative behavior of international hotel employees in Taiwan.…”
Section: Discussionmentioning
confidence: 62%
“…The results of this study indicate that hotel management should encourage knowledge sharing behavior, especially knowledge collecting to improve their employee innovative work behavior. The significant positive relationship between knowledge collecting and knowledge donating to innovative work behavior was also found by Hu et al (2009), Kim and Lee (2013), and also by Akram, Lei, Haider, and Hussain (2018). Hu et al (2009) emphasis the role of employee knowledge sharing (symbiosis, reputation, and altruism) as determinants of innovative behavior of international hotel employees in Taiwan.…”
Section: Discussionmentioning
confidence: 62%
“…(vi) Knowledge donation and collection are positively correlated with innovative work behavior. This relationship can be also mentioned by Radaelli et al (2014), Akhavan et al (2015), Jaberi (2016), Phung et al (2017), Akram et al (2018).…”
Section: Discuss Research Findingsmentioning
confidence: 69%
“…The creative theory of knowledge emphasizes interpersonal interaction to form new knowledge, which is the basis for the relationship between innovative work behavior and knowledge sharing. At the same time, previous researchers such as Radaelli et al (2014), Akhavan et al (2015), Jaberi (2016), Phung et al (2017), Akram et al (2018) affirmed in their studies the relationship between knowledge donation and collection with the act of innovation. Therefore, the hypotheses are proposed as follows:…”
Section: Knowledge Sharing and Innovative Work Behaviormentioning
confidence: 83%
“…The impact of knowledge sharing on innovative work behavior is explored in many studies. Some studies acknowledge that this relationship can be mentioned as research by Radaelli et al (2014), Akhavan et al (2015), Jaberi (2016), Phung et al (2017), Akram et al (2018). In research at telecommunications enterprises, the authors also concluded that knowledge sharing with two central processes is knowledge donation and collection related to innovative work behavior.…”
Section: Discussion and Implicationmentioning
confidence: 98%
“…,Akhavan et al (2015),Jaberi (2016),Phung et al (2017),Akram et al (2018) have confirmed that having an impact of donating and collecting knowledge on innovative work behavior. Therefore, the hypotheses are proposed as follows:Hypothesis 1 (H1): The process of donating knowledge has a positive impact on innovative work behavior.…”
mentioning
confidence: 89%